2007
DOI: 10.1177/104063870701900415
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polymerase Chain Reaction Fingerprinting to Differentiate Ornithobacterium Rhinotracheale Isolates

Abstract: Ornithobacterium rhinotracheale (ORT) is an infectious respiratory pathogen of chickens, turkeys, and wild birds. There are 18 serotypes of ORT reported worldwide. In this study, enterobacterial repetitive intergenic consensus (ERIC) polymerase chain reaction and random amplified polymorphic DNA assay with Universal M13 primer-based fingerprinting techniques were investigated for their ability to differentiate ORT isolates. The authors examined 50 field isolates and 8 reference strains of ORT for their genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The current research extends the application of ERIC-PCR, which has previously been used for typing a wide variety of gram-negative bacteria in chickens, including Arcobacter spp. (5), Escherichia coli (17), Salmonella enterica (13), Campylobacter jejuni (70), Pasteurella multocida (52), and Ornithobacterium rhinotracheale (60). Collectively, the current research and these past studies highlight the utility of ERIC-PCR in the typing of a variety of Isolates of enterococci were also able to be typed to the species and ERIC type levels, supporting a previous assessment of the ERIC-PCR for the differentiation of E. faecium isolates (18).…”
Section: Comparison Of the Rep-pcr Protocols For Representativesupporting
confidence: 78%
“…The current research extends the application of ERIC-PCR, which has previously been used for typing a wide variety of gram-negative bacteria in chickens, including Arcobacter spp. (5), Escherichia coli (17), Salmonella enterica (13), Campylobacter jejuni (70), Pasteurella multocida (52), and Ornithobacterium rhinotracheale (60). Collectively, the current research and these past studies highlight the utility of ERIC-PCR in the typing of a variety of Isolates of enterococci were also able to be typed to the species and ERIC type levels, supporting a previous assessment of the ERIC-PCR for the differentiation of E. faecium isolates (18).…”
Section: Comparison Of the Rep-pcr Protocols For Representativesupporting
confidence: 78%
“…ORT is an emerging poultry pathogen associated with respiratory disease (Murthy et al 2008). There are 18 serotypes for ORT, with the majority of chicken isolates belonging to four serotypes A, B, D and E (Chansiripornchai et al 2007;Thachil et al 2007). Haemagglutinating activity of ORT serovars has been studied by using fresh erythrocytes from different species (Vega et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…They reported that the M13 fingerprinting technique was found to be more discriminative in differentiating ORT isolates than the ERIC fingerprinting technique. They suggest that fingerprinting techniques may be a more discerning tool for characterizing ORT isolates (Thachil et al., 2007 ). In this research, the isolates showed 20 different genetic patterns based on ERIC PCR results and were classified into four different clusters.…”
Section: Discussionmentioning
confidence: 99%